Low-sulfur cation-doped ferromanganese pyrophosphate precursor, carbon-coated modified lithium ferromanganese phosphate as well as preparation method and application of low-sulfur cation-doped ferromanganese pyrophosphate precursor and carbon-coated modified lithium ferromanganese phosphate

By preparing low-sulfur type cation-doped ferromanganese pyrophosphate precursor, the problem of high sulfur content in the prior art affecting electrochemical performance is solved, and the effect of improving the tap density and cycle stability of lithium manganese ferromanganese phosphate material is achieved.

CN119569019AActive Publication Date: 2025-03-07RUYUAN DONGYANGGUANG NEW ENERGY MATERIAL CO LTD +1

Patent Information

Application Number
CN202411790663.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-07
Estimated Expiration
2044-12-06

Smart Images

  • Figure CN119569019A_ABST
    Figure CN119569019A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy materials, and particularly relates to a low-sulfur cation-doped ferromanganese pyrophosphate precursor, carbon-coated modified lithium ferromanganese phosphate as well as a preparation method and application of the low-sulfur cation-doped ferromanganese pyrophosphate precursor and carbon-coated modified lithium ferromanganese phosphate. According to the invention, the low-sulfur cation doped ferromanganese pyrophosphate precursor is successfully prepared. A proper amount of phosphoric acid source is added into the prepared metal cation doped ammonium manganese ferric phosphate precursor for treatment, so that the sulfur content is effectively reduced, the molar ratio of manganese, iron, doped elements and phosphorus elements is regulated and controlled to be slightly smaller than 1, and the tap density of the precursor is effectively improved. The precursor can effectively inhibit generation of gas in the high-temperature sintering process, the hole defect is avoided, the compactness of the structure of the prepared carbon-coated modified lithium manganese iron phosphate material is ensured, and the cycling stability of the material is remarkably improved. The lithium ion battery constructed based on the material shows excellent electrochemical performance. In addition, the precursor is simple in preparation process, high in raw material conversion rate and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology. More specifically, it relates to a low-sulfur cation-doped pyrophosphorus iron precursor, a carbon-coated modified lithium manganese iron phosphate, and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy technologies, cathode materials, as a key factor in the performance of lithium-ion batteries, are receiving more and more attention. 4 ) materials are used as positive electrode materials for lithium-ion batteries. They have been widely used in electric vehicles, energy storage systems and other fields due to their high safety, long cycle life and relatively low cost. However, their tap density is low, resulting in low volume energy density; at the same time, their electrical conductivity is relatively poor and requires the addition of conductive agents to improve it, which increases the cost to a certain extent and affects the overall performance of the battery.

[0003] At the same time, lithium iron manganese phosphate positive electrode materials have gradually emerged with their higher voltage platform, energy density and better low-temperature performance, and have become a new focus of the current industrial research and development of positive electrode materials. In recent years, strategies such as carbon coating and cation doping have become research hotspots. Among them, carbon coating can effectively improve the conductivity of the material, avoid direct contact between lithium iron manganese phosphate and electrolyte, and inhibit the excessive growth of nanoparticles during sintering; cation doping can effectively lengthen the Li-O bond in the lithium iron manganese phosphate lattice, assist lithium ion migration and improve the structural stability of the material. However, the mainstream solid-phase sintering method obtains lithium iron manganese phosphate by mixing and sintering iron element, manganese source, phosphorus source, lithium source, carbon source, and dopant according to a certain stoichiometric ratio. It cannot effectively ensure that atoms are evenly distributed in the bulk phase, thereby affecting the electrochemical performance of the positive electrode material. For example, Chinese patent application CN117715861A discloses a layer of manganese iron pyrophosphate and lithium iron manganese phosphate materials. The obtained lithium iron manganese phosphate material has excellent compaction density, and the further prepared battery also has good capacity and first effect. However, similar lithium manganese iron phosphate materials are often doped with manganese through low-cost manganese sulfate. Although this approach is economical, it will inevitably cause the problem of excessive sulfur content in the material, which in turn exacerbates the challenges of its electrochemical performance. These problems lead to unsatisfactory performance of lithium manganese iron phosphate cathode materials in terms of charge and discharge capacity and cycle stability, so the performance of lithium manganese iron phosphate materials needs to be further improved. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the prior art in that the sulfur content in the manganese iron pyrophosphate precursor is high, thereby affecting the electrochemical performance of lithium manganese iron phosphate, and to provide a method for preparing a low-sulfur cation-doped manganese iron pyrophosphate precursor.

[0005] Another object of the present invention is to provide a low-sulfur cation-doped ferromanganese pyrophosphate precursor prepared by the above preparation method.

[0006] Another object of the present invention is to provide a method for preparing carbon-coated modified lithium manganese iron phosphate.

[0007] Another object of the present invention is to provide carbon-coated modified lithium manganese iron phosphate prepared by the above preparation method.

[0008] Another object of the present invention is to provide a lithium-ion battery positive electrode, the positive electrode comprising the aforementioned carbon-coated modified lithium manganese iron phosphate.

[0009] Another object of the present invention is to provide a lithium ion battery, wherein the positive electrode of the lithium ion battery comprises the positive electrode of the lithium ion battery described above.

[0010] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0011] The present invention provides a method for preparing a low-sulfur cation-doped ferromanganese pyrophosphate precursor, comprising the following steps:

[0012] S1. Using manganese sulfate as a manganese salt to prepare a metal cation-doped ammonium manganese iron phosphate precursor;

[0013] S2. The metal cation-doped ammonium manganese iron phosphate precursor obtained in step S1 is mixed with a phosphoric acid source solution, the pH of the solution is adjusted to 7 to 11, the mixture is fully reacted at 50 to 150° C., filtered, the precipitate is washed, and dried to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor;

[0014] S3. The low-sulfur cation-doped ammonium manganese iron phosphate precursor obtained in step S2 is fully calcined at 400 to 600° C. to obtain a low-sulfur cation-doped manganese iron pyrophosphate precursor;

[0015] Wherein, the metal cation is selected from at least one non-repeating member of Mg, Ti, V, Co, Ni, Cr, Zn, Cu, Zr, Nb, Mo, Al, Ta, W, and Ca;

[0016] The expression of the low-sulfur cation-doped ferromanganese pyrophosphate precursor is (Mn x Fe 1-x-y M y ) 2 P 2 O 7 , 0<x≤0.9, 0<y≤0.1; said M represents one or more metal cation doping;

[0017] The amount of the phosphoric acid source (the amount of which is calculated as phosphate radical) added is at least 0.1 times the amount of the metal cation-doped ammonium manganese iron phosphate precursor;

[0018] Steps S1 to S3 are all performed under a protective gas atmosphere.

[0019] The manganese doping process of lithium manganese iron phosphate materials is often achieved through low-cost manganese sulfate. Although this approach is economical, it will inevitably cause the problem of excessive sulfur content in the material. This is because sulfur impurities (sulfate) will be wrapped inside the prepared metal cation-doped ammonium manganese iron phosphate precursor particles or adsorbed on the surface, resulting in a high sulfur impurity content in the resulting precursor. The inventors have discovered that adding an appropriate amount of phosphate source to the synthesized metal cation-doped ammonium manganese iron phosphate precursor can induce recrystallization to expose sulfur impurities and detach them from the precursor particles, and then through subsequent filtering and washing post-treatment, the transfer of sulfur impurities is achieved, thereby achieving the purpose of removing sulfur impurities. At the same time, the addition of a phosphate source can regulate the metal cation-doped ammonium manganese iron phosphate precursor Mn x Fe 1-x-y M y PO 4 The molar ratio of the total molar sum of manganese, iron and doped metal elements to phosphorus is slightly less than 1, which achieves uniform substitution and coordination of different elements in the precursor. This regulation ensures the regular distribution of doped metal, manganese and iron elements at the atomic level in the precursor lattice, forming a single solid solution phase, thereby further improving the structural stability of the prepared low-sulfur cation-doped manganese iron pyrophosphate precursor and greatly reducing its sulfur content.

[0020] Further, as a common expression, the (Mn x Fe 1-x-y M y ) 2 P 2 O 7 When M represents multiple (such as 4) metal cations doping, A, B, C, and D are used to represent 4 different metal cations respectively.

[0021] Furthermore, as a common expression, when the number of doped metal cations is 4, the expression of the low-sulfur cation-doped manganese iron pyrophosphate precursor is (Mn x Fe 1-x-a-b-c-d A a B b C c D d ) 2 P 2 O 7 , and 0<x≤0.9, 0<a≤0.1, 0<b≤0.1, 0<c≤0.1, 0<d≤0.1, a+b+c+d≤0.1.

[0022] Further, as a common expression, the (Mn x Fe 1-x-y M y ) 2 P 2 O 7 When M represents multiple (such as 5) metal cations doping, A, B, C, D, and E are used to represent 5 different metal cations respectively.

[0023] Furthermore, as a common expression, when the number of doped metal cations is 5, the expression of the low-sulfur cation-doped manganese iron pyrophosphate precursor is (Mn x Fe 1-x-a-b-c-d-e A a B b C c D d E e ) 2 P 2 O 7 , and 0<x≤0.9, 0<a≤0.1, 0<b≤0.1, 0<c≤0.1, 0<d≤0.1, 0<e≤0.1, a+b+c+d+e≤0.1.

[0024] Furthermore, in step S1, the method for preparing the metal cation-doped ammonium manganese iron phosphate precursor specifically comprises the following steps:

[0025] SI. Preparation of a mixed solution containing manganese sulfate and a doped metal cation salt I;

[0026] SII. The iron element and the phosphoric acid source solution are mixed and reacted sufficiently to obtain a ferrous dihydrogen phosphate solution system II;

[0027] SIII. At 70-150° C., the mixed solution I obtained in step SI and the oxidant are added to the ferrous dihydrogen phosphate solution system II obtained in step SII, mixed and reacted sufficiently to oxidize the divalent manganese ions and the divalent iron ions to trivalent manganese ions and trivalent iron ions, respectively, to obtain an intermediate system III, adjust the pH to 7-11, react sufficiently, and post-treat to obtain a metal cation-doped ammonium manganese iron phosphate precursor;

[0028] Wherein, steps SI to SIII are all carried out under a protective gas atmosphere.

[0029] Furthermore, in step S1, the metal cation salt includes one or more of sulfate, chloride, nitrate, acetate, ammonium salt, carbonate, phosphate, oxalate, basic salt, and alcohol salt.

[0030] Further, in step S1, the Mg is selected from one or more of magnesium chloride, magnesium sulfate, magnesium chloride, magnesium acetate, magnesium nitrate, magnesium oxalate, magnesium carbonate, and magnesium citrate.

[0031] Furthermore, in step S1, the Ti is selected from one or more of titanium sulfate, titanium chloride, ammonium titanium oxalate, and titanium sulfate.

[0032] Further, in step SI, the V is selected from one or more of vanadium oxysulfate, vanadium oxychloride, vanadium oxalate, and vanadium oxyoxalate.

[0033] Furthermore, in step S1, the Co is selected from one or more of cobalt sulfate, cobalt chloride, cobalt acetate, and cobalt nitrate.

[0034] Furthermore, in step S1, the Ni is selected from one or more of nickel sulfate, nickel chloride, nickel acetate, and nickel nitrate.

[0035] Furthermore, in step S1, the Cr is selected from one or more of chromium sulfate, chromium chloride, chromium acetate, and chromium oxalate.

[0036] Furthermore, in step S1, the Zn is selected from one or more of zinc sulfate, zinc chloride, zinc acetate, zinc oxalate, and zinc nitrate.

[0037] Further, in step S1, the Cu is selected from one or more of copper sulfate, copper chloride, copper acetate, and copper nitrate.

[0038] Furthermore, in step S1, the Zr is selected from one or more of zirconium sulfate, zirconium tetrachloride, zirconium acetate, zirconium oxychloride, and zirconium nitrate.

[0039] Furthermore, in step S1, the Nb is selected from ammonium niobium oxalate and / or niobium oxalate.

[0040] Further, in step S1, the Mo is selected from one or more of molybdenum sulfate, molybdenum chloride, molybdenum acetate, ammonium molybdate, and molybdenum nitrate.

[0041] Furthermore, in step S1, the Al is selected from one or more of aluminum sulfate, aluminum chloride, and aluminum nitrate.

[0042] Furthermore, in step S1, the Ta is selected from one or more of tantalum sulfate, tantalum pentachloride, tantalum ethoxide, tantalum butoxide, and tantalum isopropoxide.

[0043] Furthermore, in step S1, the W is selected from one or more of tungsten nitrate, tungsten chloride, and tungsten phosphate.

[0044] Further, in step SI, the Ca is selected from one or more of calcium bicarbonate, calcium dihydrogen phosphate, calcium chloride, calcium acetate, and calcium nitrate.

[0045] Further, in step SI, the molar ratio of manganese in the manganese sulfate to the doped metal in the doped metal cation salt M solution is f:g, where 0 < f ≤ 0.9 and 0 < g ≤ 0.1.

[0046] Further, in step SI, the concentration of the mixed solution I is the molar concentration of the total metal cations.

[0047] Furthermore, in step SI, the concentration of the mixed solution I is 0.1 - 10 mol / L, preferably 3 mol / L.

[0048] Further, in step SI, the protective gas includes one or more of nitrogen, helium, and argon.

[0049] Further, in step SII, the elemental iron is derived from one or more of iron blocks, iron powders, and iron sheets.

[0050] Further, in step SII, the phosphoric acid source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium dihydrogen phosphate, disodium hydrogen phosphate, lithium dihydrogen phosphate, ammonium phosphate, lithium phosphate, sodium phosphate, ammonium hypophosphite, ammonium polyphosphate, sodium phosphite, sodium metaphosphate, and sodium tripolyphosphate.

[0051] Further, in step SII, the molar ratio of the elemental iron to the phosphoric acid source is 1:(2 - 5).

[0052] Further, in step SII, the time for sufficient reaction is 0.5 - 20 h.

[0053] Further, in step SII, since the oxidizing property of the phosphoric acid source is weak and in an atmosphere of protective gas, the elemental iron is only oxidized to the divalent state, and thus ferrous dihydrogen phosphate is formed.

[0054] Further, in step SIII, the oxidant includes one or more of hydrogen peroxide, oxygen, and ozone. Adding an oxidant, one of the purposes is to oxidize Mn in the divalent manganese salt in the mixed solution I obtained in step SI to Mn 2+ ; the second purpose is to oxidize Fe in the ferrous dihydrogen phosphate solution system II obtained in step SII to Fe 3+ ; 2+ to Fe 3+ .

[0055] Further, in step SIII, the molar ratio of the oxidant is at least 0.5 times the molar amount of the divalent manganese salt in the mixed solution I obtained in step SI.

[0056] Furthermore, in step SIII, the sufficient reaction time is 2 to 36 hours.

[0057] Furthermore, in step SIII, the pH 7-11 is adjusted by adding an alkaline agent.

[0058] Furthermore, the alkaline reagent includes one or more of urea, ammonia, and urea phosphate. By using these alkaline reagents to adjust the solution pH, Mn 3+ and Fe 3+ It is co-precipitated with the doped metal cations in the phosphate system to form a uniform metal cation-doped ammonium manganese iron phosphate precursor, while also avoiding the use of sodium hydroxide, potassium hydroxide, etc. to introduce alkali metal impurities such as Na and K.

[0059] Furthermore, in step SIII, the post-treatment includes filtering, washing and drying.

[0060] Furthermore, the filtration is filter pressing, that is, the solution containing the metal cation-doped ammonium manganese ferric phosphate precursor is filtered by filter pressing and then solid-liquid separation is performed to obtain a filter cake.

[0061] Furthermore, the washing is washing the filter cake after the filter pressing with water for 3 to 5 times.

[0062] Furthermore, the drying is flash evaporation, that is, the washed filter cake is transferred into a flash evaporator for heat and moisture exchange to quickly evaporate the surface moisture.

[0063] Specifically, in step SIII, the post-treatment includes filtering the solution containing the metal cation-doped ammonium manganese iron phosphate precursor and then separating the solid and liquid, washing the filter cake after filtering with water for 3 to 5 times, and transferring the washed filter cake into a flash evaporator for wet heat exchange to quickly evaporate the surface moisture.

[0064] Furthermore, in step S2, the phosphate source includes one or more of phosphoric acid, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, lithium dihydrogen phosphate, lithium phosphate, ammonium hypophosphite, and ammonium polyphosphate.

[0065] Furthermore, in step S2, the molar ratio of the metal cation-doped ammonium manganese iron phosphate precursor to the phosphoric acid source is 1: (0.1-20), and this ratio is intended to ensure that the phosphoric acid source is excessive relative to the precursor. If the phosphoric acid source is added in excessive amounts, it will cause unnecessary waste of resources.

[0066] Furthermore, in step S2, the mixing time is 0.5 to 20 hours.

[0067] Furthermore, in step S2, the pH value of 7 to 11 is adjusted by adding an alkaline reagent.

[0068] Furthermore, the alkaline reagent includes one or more of urea, ammonia water, and urea phosphate.

[0069] Furthermore, in step S2, the sufficient reaction time is 2 to 36 hours.

[0070] Furthermore, in step S2, the filtration is filter pressing, that is, the solution containing the low-sulfur cation-doped ammonium manganese iron phosphate precursor is filtered pressing and then solid-liquid separation is performed.

[0071] Furthermore, in step S2, the precipitate washing is washing the filtered precipitate with water for 3 to 5 times.

[0072] Furthermore, in step S2, the drying is flash evaporation, that is, the washed precipitate is transferred into a flash evaporator for heat and moisture exchange to quickly evaporate surface moisture.

[0073] Furthermore, in step S3, the sufficient calcination time is 1 to 4 hours.

[0074] The present invention protects the low-sulfur cation-doped ferromanganese pyrophosphate precursor prepared by the above preparation method.

[0075] The present invention provides a method for preparing carbon-coated modified lithium manganese iron phosphate, comprising the following steps:

[0076] Si. The lithium salt, the phosphate source, the aforementioned low-sulfur cation-doped ferromanganese pyrophosphate precursor, the carbon source and the alcohol solution are fully mixed to obtain a slurry, and the obtained slurry is ground and dried to obtain a powder;

[0077] Sii. Under a protective gas atmosphere, the powder obtained in step Si is pre-calcined at 450-550° C. for 0.5-8 h, then heated to 650-900° C. for sufficient calcination, and post-treated to obtain carbon-coated modified lithium manganese iron phosphate.

[0078] This application uses low-sulfur cation-doped pyrophosphate manganese iron as a precursor for preparing carbon-coated modified manganese iron lithium phosphate materials. Its significant advantage is that during the high-temperature sintering process, it can effectively prevent the generation of gas, thereby avoiding the formation of void defects and ensuring the compactness of the carbon-coated modified manganese iron lithium phosphate material structure. This feature not only effectively improves the compaction density of the material, but also alleviates the problem of manganese dissolution, thereby greatly improving the material's cycle stability. Compared with the traditional ammonium manganese iron phosphate precursor, it will decompose and produce ammonia during high-temperature sintering, causing the material to form a loose and porous structure, which is not conducive to improving the compaction density and subsequent battery performance optimization.

[0079] Furthermore, in step Si, the lithium salt includes one or more of lithium carbonate, lithium dihydrogen phosphate, dilithium hydrogen phosphate, lithium phosphate, lithium hydroxide, lithium nitrate, and lithium acetate.

[0080] Furthermore, in step Si, the phosphate source includes one or more of lithium dihydrogen phosphate, lithium phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, ammonium phosphate, phosphoric acid, ammonium hypophosphite, and ammonium polyphosphate.

[0081] Furthermore, in step Si, the carbon source includes one or more of polyethylene glycol, polyethylene diene, polyvinyl alcohol, glucose, fructose, sucrose, starch, graphene oxide, polyvinyl pyrrolidone, polyvinylidene fluoride, lauric acid, ascorbic acid, and citric acid.

[0082] Furthermore, in step Si, the molar ratio of the lithium salt, the phosphoric acid source, and the low-sulfur type cation-doped ferromanganese pyrophosphate precursor obtained above is 1: (0.8-1.2): (0.9-1.1). The lithium salt and the phosphoric acid source are appropriately added in excess to ensure that the reaction is fully and completely carried out.

[0083] Furthermore, in step Si, the mass ratio of the low-sulfur type cation-doped ferromanganese pyrophosphate precursor to the carbon source is 1:(0.01-1).

[0084] Furthermore, in step S1, the alcohol solution is a mixed solution of an alcohol reagent and water, wherein the alcohol reagent not only serves as a dispersion medium, but also contributes to the rapid drying of the solution due to its faster volatilization rate.

[0085] Furthermore, the alcohol reagent includes one or more of ethanol, methanol, and ethylene glycol.

[0086] Preferably, the alcohol reagent is ethanol.

[0087] More preferably, the volume ratio of the alcohol reagent to water is 1:(1-5).

[0088] Furthermore, in step Si, the solid content of the slurry is 10% to 45%.

[0089] Furthermore, in step Si, the particle size of the ground slurry is 0.35 μm ≤ D 50 ≤0.4μm.

[0090] Furthermore, in step Si, the drying is spray drying.

[0091] Furthermore, the spray drying conditions are as follows: the inlet air temperature is 200-260°C, the outlet air temperature is 90-110°C, and the outlet particle size is 6 μm ≤ D 50 ≤9μm.

[0092] Furthermore, in step Sii, the protective gas includes one or more of nitrogen, helium, and argon.

[0093] Furthermore, in step Sii, the calcining equipment is a box furnace, a roller kiln or a tube furnace, preferably a box furnace.

[0094] Furthermore, the heating rate of the calcination is 1 to 10°C / min.

[0095] Furthermore, in step Sii, the sufficient calcination time is 2 to 20 hours. The staged calcination method is conducive to the formation of a single phase of the carbon-coated modified lithium manganese iron phosphate.

[0096] The present invention protects the carbon-coated modified lithium manganese iron phosphate prepared by the above preparation method.

[0097] The carbon-coated modified lithium iron manganese phosphate material prepared in this application presents a single solid solution phase structure. This feature ensures that there is no mixing of iron, manganese and manganese-iron related phases in the material, thereby ensuring that the structural stability, compaction density and conductivity of the material are not affected. In addition, the doped cations are evenly distributed in the lithium iron manganese phosphate material, rather than locally aggregated or distributed only on the surface. This optimized distribution pattern fundamentally improves the electronic structure and electrochemical properties of lithium iron manganese phosphate, avoids the problem of insufficient performance adjustment, and provides a strong guarantee for the high performance of the battery.

[0098] The present invention protects a lithium ion battery positive electrode, comprising a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material comprises the above-mentioned carbon-coated modified lithium manganese iron phosphate.

[0099] Preferably, the current collector is aluminum foil or carbon-coated aluminum foil.

[0100] Furthermore, as a preferred manner, the preparation method of the positive electrode of the lithium-ion battery comprises the following steps: dispersing carbon-coated modified lithium manganese iron phosphate, conductive agent carbon black, and binder polyvinylidene fluoride in N-methylpyrrolidone dispersant to obtain a positive electrode slurry, then coating it on aluminum foil, and vacuum drying it at 80 to 140° C. for 12 to 24 hours to obtain a positive electrode.

[0101] Furthermore, the mass ratio of the carbon-coated modified lithium manganese iron phosphate, the conductive agent carbon black, and the binder polyvinylidene fluoride is 1: (0.03-0.125): (0.03-0.125).

[0102] The present invention protects a lithium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode of the lithium ion battery mentioned above.

[0103] The lithium ion battery prepared by the present invention exhibits excellent compaction density, charge and discharge capacity, capacity retention rate and cycle stability.

[0104] Furthermore, as a preferred embodiment, the positive electrode of the lithium-ion battery is the positive electrode of the lithium-ion battery described above, the negative electrode is a metal lithium sheet, the separator is a polyethylene film, and the electrolyte is 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0105] Compared with the prior art, the present invention has the following beneficial effects:

[0106] The present application provides a low-sulfur cation-doped manganese iron pyrophosphate precursor. By adding an appropriate amount of phosphoric acid source to the prepared metal cation-doped ammonium manganese iron phosphate precursor, not only the sulfur content is effectively reduced, but also the molar ratio of manganese, iron, doping elements and phosphorus elements is regulated to be slightly less than 1, which effectively improves the tap density of the precursor. This precursor can effectively suppress gas generation during high-temperature sintering, avoid pore defects, ensure the compactness of the structure of the obtained carbon-coated modified manganese iron lithium phosphate material, and significantly improve the cyclic stability of the material. The lithium-ion battery constructed based on this material exhibits excellent electrochemical properties. In addition, the preparation process of the precursor is simple, the raw material conversion rate is high, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0107] Figure 1 The low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 SEM image of .

[0108] Figure 2 The low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.7 Fe 0.25 Mg 0.01 V 0.0 1 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 SEM image of .

[0109] Figure 3 The low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti0.02 V 0.03 ) 2 P 2 O 7 SEM image of the precursor. DETAILED DESCRIPTION

[0110] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0111] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0112] Example 1 A low-sulfur cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0113] 1. Low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 Preparation

[0114] Ultrapure water was added to a dissolving tank filled with nitrogen, and 16.81 kg of manganese sulfate monohydrate, 730.9 g of sodium tungstate, 664 g of vanadium oxalate, 1338.1 g of niobium oxalate, 236.8 g of anhydrous magnesium chloride, and 161.5 g of anhydrous cobalt chloride were dissolved in the above dissolving tank to prepare a 3 mol / L metal salt mixed solution I.

[0115] 766g of iron powder was added to a closed synthesis reactor containing 8.2L of ultrapure water, the temperature of the reactor was set to 40°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 14.34kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 76°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (7.69kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 384.4g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.3, and then the intermediate system IV was aged at 76°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 125 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0116] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Put it into a high-efficiency sealed synthesis reactor with 20L ultrapure water as the base liquid to break up the slurry, slowly pump 85wt% concentrated phosphoric acid solution into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stir for 30 minutes to obtain the intermediate system V, then use ammonia water to adjust the system V to pH 7.3, and then age the system V for 4 hours. Finally, use a vertical filter press to filter the obtained slurry to obtain a filter cake, and use high-purity water to wash until the conductivity of the washing water is 108μs / cm, and then flash evaporate to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.8 Fe 0.1 1 W 0.02 V0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0117] Doping the low-sulfur cation with the ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 The low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 ).

[0118] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Preparation

[0119] The corresponding lithium carbonate, lithium dihydrogen phosphate, low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn) were weighed with a ratio of Li:P:(Mn+Fe+W+V+Nb+Mg+Co) of 1.1:1.03:1. 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 Polyethylene glycol and glucose (6.5 wt% of low-sulfur cation-doped manganese iron phosphate precursor, and the mass ratio of polyethylene glycol to glucose is 2:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 35%, and the above slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system.50 When the particle size was 0.38 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 4 hours. Then, the temperature was raised to 760°C at a heating rate of 10°C / min and kept for 10 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0120] 3. Preparation of Lithium-ion Batteries

[0121] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0122] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0123] Example 2 A low-sulfur cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0124] 1. Low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 Preparation

[0125] Ultrapure water was added to a dissolving tank filled with nitrogen, and 6.47 kg of manganese sulfate monohydrate, 65.9 g of magnesium sulfate, 146.1 g of vanadium oxalate, 160.8 g of sodium tungstate, 88.3 g of zinc sulfate, and 187.2 g of aluminum sulfate were dissolved in the above dissolving tank to prepare a 2 mol / L metal salt mixed solution I.

[0126] 766g of iron powder was added to a closed synthesis reactor containing 16.2L of ultrapure water, the temperature of the reactor was set to 45°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 6.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 75°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (3.38kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 169.1g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.8, and then the intermediate system IV was aged at 75°C for 2 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 144 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 ).

[0127] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 The mixture was put into a high-efficiency sealed synthesis reactor with 20L ultrapure water as the base liquid to break up the slurry. 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stirred for 30 minutes to obtain the intermediate system V. Then, the system V was adjusted to pH 7.8 with ammonia water, and the intermediate system V was aged for 4 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, and washed with high-purity water until the conductivity of the washing water was 112μs / cm, and then flash evaporated to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.7 Fe 0.25 Mg0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 ).

[0128] Doping the low-sulfur cation with the ammonium manganese iron phosphate precursor NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 The mixture was placed in a graphite crucible and heated to 450°C in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm) at a heating rate of 10°C / min and kept at that temperature for 3 h to prepare a low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 ).

[0129] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 Preparation

[0130] The corresponding lithium carbonate, lithium dihydrogen phosphate, low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn) were weighed with a ratio of Li:P:(Mn+Fe+Mg+V+W+Zn+Al) of 1.08:1.04:1. 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7Polyethylene glycol and glucose (5.9 wt% low-sulfur cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 3:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 38%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50 When the particle size was 0.39 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 550°C at a heating rate of 5°C / min and kept for 5 hours. Then, the temperature was raised to 720°C at a heating rate of 10°C / min and kept for 9 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 ).

[0131] 3. Preparation of Lithium-ion Batteries

[0132] The carbon-coated modified lithium manganese iron phosphate, conductive agent carbon black, and binder polyvinylidene fluoride obtained above were dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which was then coated on aluminum foil and dried in vacuum at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0133] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0134] Example 3 A low-sulfur cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0135] 1. Low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 Preparation

[0136] Ultrapure water was added to a dissolving tank filled with nitrogen, and 1.68 kg of manganese sulfate monohydrate, 147.3 g of ammonium titanium oxalate, and 199.2 g of vanadium oxalate were dissolved in the above dissolving tank to prepare a 2 mol / L metal salt mixed solution I.

[0137] 766g of iron powder was added to a closed synthesis reactor containing 19.1L of ultrapure water, the temperature of the reactor was set to 50°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 2.87kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 72°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (1.54kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 76.9g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7, and then the intermediate system IV was aged at 72°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 153 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 ).

[0138] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 The mixture was put into a high-efficiency sealed synthesis reactor with 20L ultrapure water as the base liquid to break up the slurry. 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stirred for 30 minutes to obtain the intermediate system V. Then, ammonia water was used to adjust the pH of system V to 7, and system V was aged for 4 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, and washed with high-purity water until the conductivity of the washing water was 126μs / cm, and then flash-evaporated to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V0.03 PO 4 ).

[0139] Doping the low-sulfur cation with the ammonium manganese iron phosphate precursor NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 The mixture was placed in a graphite crucible and heated to 500°C in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm) at a heating rate of 10°C / min and kept at this temperature for 3 h to prepare a low-sulfur cation-doped manganese iron pyrophosphate precursor ((Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 ).

[0140] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 Preparation

[0141] The corresponding lithium carbonate, lithium dihydrogen phosphate, low-sulfur type cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 Polyethylene glycol and glucose (5.9 wt% low-sulfur cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 4:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 38%. The slurry is coarsely ground and finely ground to a particle size of D using a horizontal sand mill system. 50 When the particle size was 0.37 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages in an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 5 hours. Then, the temperature was raised to 700°C at a heating rate of 10°C / min and kept for 9 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO4 ).

[0142] 3. Preparation of Lithium-ion Batteries

[0143] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0144] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0145] Example 4 A low-sulfur cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0146] 1. Low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.6 Fe 0.35 Ti 0.05 ) 2 P 2 O 7 Preparation

[0147] Ultrapure water was added to a dissolving tank filled with nitrogen, and 3.96 kg of manganese sulfate monohydrate and 539.2 g of ammonium titanyl oxalate were dissolved in the dissolving tank to prepare a 1 mol / L metal salt mixed solution I.

[0148] 766g of iron powder was added to a closed synthesis reactor containing 22.3L of ultrapure water, the temperature of the reactor was set to 40°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 4.51kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 78°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (2.42kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 120.8g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.2, and then the intermediate system IV was aged at 78°C for 2h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 141μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.6 Fe 0.35 Ti 0.05 PO 4 ).

[0149] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.6 Fe 0.35 Ti 0.05 PO 4 Put it into a high-efficiency sealed synthesis reactor with 20L ultrapure water as the base liquid to break up the slurry, slowly pump 85wt% concentrated phosphoric acid solution into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stir for 30 minutes to obtain the intermediate system V, then use ammonia water to adjust the system V to pH 7.2, and then age the system V for 4 hours. Finally, use a vertical filter press to filter the obtained slurry to obtain a filter cake, and use high-purity water to wash until the conductivity of the washing water is 136μs / cm, and then flash evaporate to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.6 Fe 0.35 Ti 0.05 PO 4 ).

[0150] Doping the low-sulfur cation with the ammonium manganese iron phosphate precursor NH 4 Mn 0.6 Fe 0.35 Ti 0.0 PO4 The mixture was placed in a graphite crucible and heated to 480°C in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm) at a heating rate of 10°C / min for 3 h to prepare a low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.6 Fe 0.35 Ti 0.05 ) 2 P 2 O 7 ).

[0151] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.6 Fe 0.35 Ti 0.05 PO 4 Preparation

[0152] The corresponding lithium carbonate, lithium dihydrogen phosphate, low-sulfur type cation-doped manganese iron pyrophosphate precursor (Mn 0.6 Fe 0.35 Ti 0.05 ) 2 P 2 O 7 Polyethylene glycol and glucose (7.2 wt% low-sulfur cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 2.5:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 38%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50 When the particle size is 0.38 μm, the slurry is transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, in a nitrogen protective atmosphere, the spray powder is sintered in stages using an atmosphere box furnace. The temperature is raised to 520°C at a heating rate of 5°C / min and kept for 5 hours, and then the temperature is raised to 760°C at a heating rate of 10°C / min and kept for 9 hours. After the atmosphere box furnace is naturally cooled to room temperature, the obtained furnace sintered powder is sieved to obtain carbon-coated modified lithium manganese iron phosphate (LiMn 0.6 Fe 0.35 Ti 0.05 PO 4 ).

[0153] 3. Preparation of Lithium-ion Batteries

[0154] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0155] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0156] Comparative Example 1 A cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0157] The difference from Example 1 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with an appropriate amount of phosphate source, that is, the low-sulfur type cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 .

[0158] 1. Cation-doped manganese iron pyrophosphate precursor (Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 Preparation

[0159] Ultrapure water was added to a dissolving tank filled with nitrogen, and 16.81 kg of manganese sulfate monohydrate, 730.9 g of sodium tungstate, 664 g of vanadium oxalate, 1338.1 g of niobium oxalate, 236.8 g of anhydrous magnesium chloride, and 161.5 g of anhydrous cobalt chloride were dissolved in the above dissolving tank to prepare a 3 mol / L metal salt mixed solution I.

[0160] 766g of iron powder was added to a closed synthesis reactor containing 8.2L of ultrapure water, the temperature of the reactor was set to 40°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 14.34kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 76°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (7.69kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 384.4g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.3, and then the intermediate system IV was aged at 76°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 125 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0161] Doping of ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 The cation-doped manganese iron pyrophosphate precursor (Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 ) 2 P 2 O 7 ).

[0162] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.8 Fe0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Preparation

[0163] The corresponding lithium carbonate, lithium dihydrogen phosphate, cation-doped manganese iron pyrophosphate precursor (Mn) were weighed with a ratio of Li:P:(Mn+Fe+W+V+Nb+Mg+Co) of 1.1:1.03:1. 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0. 01 ) 2 P 2 O 7 Polyethylene glycol and glucose (6.5 wt% cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 2:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 35%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50 When the particle size was 0.38 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 4 hours. Then, the temperature was raised to 760°C at a heating rate of 10°C / min and kept for 10 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0164] 3. Preparation of Lithium-ion Batteries

[0165] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0166] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0167] Comparative Example 2 A cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0168] The difference from Example 2 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with an appropriate amount of phosphate source, that is, the low-sulfur type cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.0 1 W 0.01 Zn 0.01 Al 0.01 PO 4 .

[0169] 1. Cation-doped manganese iron pyrophosphate precursor (Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 Preparation

[0170] Ultrapure water was added to a dissolving tank filled with nitrogen, and 6.47 kg of manganese sulfate monohydrate, 65.9 g of magnesium sulfate, 146.1 g of vanadium oxalate, 160.8 g of sodium tungstate, 88.3 g of zinc sulfate, and 187.2 g of aluminum sulfate were dissolved in the above dissolving tank to prepare a 2 mol / L metal salt mixed solution I.

[0171] 766g of iron powder was added to a closed synthesis reactor containing 16.2L of ultrapure water, the temperature of the reactor was set to 45°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 6.31kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 75°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (3.38kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 169.1g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.8, and then the intermediate system IV was aged at 75°C for 2 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 144 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 ).

[0172] Doping of ammonium manganese iron phosphate precursor NH 4 Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 The cation-doped manganese iron pyrophosphate precursor (Mn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 ).

[0173] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.7 Fe0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 Preparation

[0174] The corresponding lithium carbonate, lithium dihydrogen phosphate, cation-doped manganese iron pyrophosphate precursor (Mn) were weighed with a ratio of Li:P:(Mn+Fe+Mg+V+W+Zn+Al) of 1.08:1.04:1. 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 ) 2 P 2 O 7 Polyethylene glycol and glucose (5.9 wt% cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 3:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 38%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50 When the particle size was 0.39 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 550°C at a heating rate of 5°C / min and kept for 5 hours. Then, the temperature was raised to 720°C at a heating rate of 10°C / min and kept for 9 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.7 Fe 0.25 Mg 0.01 V 0.01 W 0.01 Zn 0.01 Al 0.01 PO 4 ).

[0175] 3. Preparation of Lithium-ion Batteries

[0176] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0177] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0178] Comparative Example 3 A cation-doped manganese iron pyrophosphate precursor, carbon-coated modified manganese iron phosphate, lithium ion battery and preparation method thereof

[0179] The difference from Example 3 is that in step 1, the metal cation-doped ammonium manganese iron phosphate precursor is not treated with an appropriate amount of phosphoric acid source, that is, the low-sulfur type cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 .

[0180] 1. Cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 Preparation

[0181] Ultrapure water was added to a dissolving tank filled with nitrogen, and 1.68 kg of manganese sulfate monohydrate, 137.3 g of ammonium titanium oxalate, and 199.2 g of vanadium oxalate were dissolved in the above dissolving tank to prepare a 2 mol / L metal salt mixed solution I.

[0182] 766g of iron powder was added to a closed synthesis reactor containing 19.1L of ultrapure water, the temperature of the reactor was set to 50°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 2.87kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 72°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (1.54kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 76.9g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7, and then the intermediate system IV was aged at 72°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 153 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 ).

[0183] Doping of ammonium manganese iron phosphate precursor NH 4 Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 The cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 ).

[0184] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 Preparation

[0185] The corresponding lithium carbonate, lithium dihydrogen phosphate, cation-doped manganese iron pyrophosphate precursor (Mn 0.4 Fe 0.55 Ti 0.02 V 0.03 ) 2 P 2 O 7 Polyethylene glycol and glucose (5.9 wt% cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 4:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 38%. The slurry is coarsely ground and finely ground to a particle size of D using a horizontal sand mill system. 50 When the particle size was 0.37 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages in an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 5 hours. Then, the temperature was raised to 700°C at a heating rate of 10°C / min and kept for 9 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.4 Fe 0.55 Ti 0.02 V 0.03 PO 4 ).

[0186] 3. Preparation of Lithium-ion Batteries

[0187] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0188] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0189] Comparative Example 4 A low-sulfur cation-doped ammonium manganese iron phosphate precursor, carbon-coated modified lithium manganese iron phosphate, lithium ion battery and preparation method thereof

[0190] The difference from Example 1 is that in step 2, the carbon-coated modified lithium manganese iron phosphate is prepared by directly doping the ammonium manganese iron phosphate precursor with low-sulfur cations.

[0191] 1. Low-sulfur cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Preparation

[0192] Ultrapure water was added to a dissolving tank filled with nitrogen, and 16.81 kg of manganese sulfate monohydrate, 730.9 g of sodium tungstate, 664 g of vanadium oxalate, 1338.1 g of niobium oxalate, 236.8 g of anhydrous magnesium chloride, and 161.5 g of anhydrous cobalt chloride were dissolved in the above dissolving tank to prepare a 3 mol / L metal salt mixed solution I.

[0193] 766g of iron powder was added to a closed synthesis reactor containing 8.2L of ultrapure water, the temperature of the reactor was set to 40°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 14.34kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 76°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (7.69kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 384.4g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of system IV to 7.3, and then the intermediate system IV was aged at 76°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 125 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0194] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.8 Fe 0.11 W 0.02 V0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 The precursor was put into a high-efficiency sealed synthesis reactor with 20L ultrapure water as the base liquid to be dispersed and slurried. 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stirred for 30 minutes to obtain intermediate system V. Then, ammonia water was used to adjust the intermediate system V to a pH of 7.3, and the intermediate system V was aged for 4 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, and washed with high-purity water until the conductivity of the washing water was 108μs / cm, and then flashed to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0195] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Preparation

[0196] The corresponding lithium carbonate, lithium dihydrogen phosphate, and low-sulfur cation-doped manganese iron pyrophosphate precursor NH were weighed with a ratio of Li:P:(Mn+Fe+W+V+Nb+Mg+Co) of 1.1:1.03:1. 4 Mn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 Polyethylene glycol and glucose (6.5 wt% low-sulfur cation-doped pyrophosphate manganese iron precursor, and the mass ratio of polyethylene glycol to glucose is 2:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 35%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50When the particle size was 0.28 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 4 hours. Then, the temperature was raised to 760°C at a heating rate of 10°C / min and kept for 10 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.8 Fe 0.11 W 0.02 V 0.02 Nb 0.02 Mg 0.02 Co 0.01 PO 4 ).

[0197] 3. Preparation of Lithium-ion Batteries

[0198] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0199] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0200] Comparative Example 5 Preparation of low-sulfur cation-doped manganese iron pyrophosphate precursor, carbon-coated modified lithium manganese iron phosphate and lithium ion battery

[0201] The difference from Example 1 is that in step 1, an excess of cation doping ratio is used to prepare a low-sulfur cation-doped ferromanganese pyrophosphate precursor.

[0202] 1. Low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 ) 2 P 2 O 7 Preparation

[0203] Ultrapure water was added to a dissolving tank filled with nitrogen, and 14.92 kg of manganese sulfate monohydrate, 1461.5 g of sodium tungstate, 1327.9 g of vanadium oxalate, 1338.1 g of niobium oxalate, 473.6 g of anhydrous magnesium chloride, and 322.9 g of anhydrous cobalt chloride were dissolved in the above dissolving tank to prepare a 3 mol / L metal salt mixed solution I.

[0204] 766g of iron powder was added to a closed synthesis reactor containing 8.2L of ultrapure water, the temperature of the reactor was set to 40°C, nitrogen was introduced into the reactor and stirred at a speed of 800r / min for 10min, and then 14.34kg of 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor, and then stirred evenly for 3h to form a ferrous dihydrogen phosphate solution system II. The reactor was then heated to 76°C, and after the system temperature was stabilized, the metal in the mixed metal source solution I: hydrogen peroxide (7.69kg 27.5wt%) was slowly pumped into the ferrous dihydrogen phosphate solution system II in a molar ratio of 2:1, and after the two were completely pumped into the ferrous dihydrogen phosphate solution system II to form an intermediate system III, the intermediate system III was fully stirred and reacted for 30min, and then 384.4g of 27.5wt% hydrogen peroxide solution was pumped into the same feed rate as above to form an intermediate system IV. Ammonia water was used to adjust the pH of the intermediate system IV to 7.3, and then the intermediate system IV was aged at 76°C for 2 h. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, which was washed with high-purity water until the conductivity of the washing water was 167 μs / cm, and then flash-evaporated to obtain a dry metal cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4 ).

[0205] Under a nitrogen atmosphere, the metal cation-doped ammonium manganese iron phosphate precursor NH 4 Mn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4The precursor was put into a high-efficiency closed synthesis reactor with 20L ultrapure water as the base liquid to break up the slurry. 85wt% concentrated phosphoric acid solution was slowly pumped into the reactor at a molar ratio of precursor: phosphoric acid = 2:1, and stirred for 30 minutes to obtain the intermediate system V. Then, ammonia water was used to adjust the pH of system V to 7.3, and system V was aged for 4 hours. Finally, the obtained slurry was filtered using a vertical filter press to obtain a filter cake, and washed with high-purity water until the conductivity of the washing water was 153μs / cm, and then flashed to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor (NH 4 Mn 0.7 1 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4 ).

[0206] Doping the low-sulfur cation with the ammonium manganese iron phosphate precursor NH 4 Mn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4 The mixture was placed in a graphite crucible and heated to 400°C in a nitrogen atmosphere box furnace (oxygen content less than 10 ppm) at a heating rate of 10°C / min and kept at that temperature for 2 h to prepare a low-sulfur cation-doped manganese iron pyrophosphate precursor ((Mn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.0 4 Mg 0.04 Co 0.02 ) 2 P 2 O 7 ).

[0207] 2. Carbon-coated modified lithium iron manganese phosphate LiMn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4 Preparation

[0208] The corresponding lithium carbonate, lithium dihydrogen phosphate, low-sulfur cation-doped manganese iron pyrophosphate precursor (Mn) were weighed with a ratio of Li:P:(Mn+Fe+W+V+Nb+Mg+Co) of 1.1:1.03:1. 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 ) 2 P 2 O 7 Polyethylene glycol and glucose (6.5 wt% low-sulfur cation-doped ferromanganese pyrophosphate precursor, and the mass ratio of polyethylene glycol to glucose is 3:1) are dispersed in ultrapure water and ethanol (the volume ratio of ultrapure water to ethanol is 2:1) to obtain a slurry with a solid content of 35%. The slurry is coarsely ground and finely ground to a particle size D using a horizontal sand mill system. 50 When the particle size was 0.28 μm, the slurry was transferred to a spray granulation dryer for spray drying to obtain a spray powder. Subsequently, the spray powder was sintered in stages using an atmosphere box furnace under a nitrogen atmosphere. The temperature was raised to 500°C at a heating rate of 5°C / min and kept for 4 hours. Then, the temperature was raised to 760°C at a heating rate of 10°C / min and kept for 10 hours. After the atmosphere box furnace was naturally cooled to room temperature, carbon-coated modified lithium manganese iron phosphate (LiMn 0.71 Fe 0.11 W 0.04 V 0.04 Nb 0.04 Mg 0.04 Co 0.02 PO 4 ).

[0209] 3. Preparation of Lithium-ion Batteries

[0210] The carbon-coated modified lithium manganese iron phosphate obtained above, the conductive agent carbon black, and the binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone dispersant in a mass ratio of 94:3:3 and mixed evenly to obtain a positive electrode slurry, which is then coated on aluminum foil and vacuum dried at 105°C for 24 hours to obtain a lithium-ion battery positive electrode.

[0211] The button lithium-ion battery was assembled in an argon-filled glove box. The positive electrode was the positive electrode of the above-mentioned lithium-ion battery, the negative electrode was a metal lithium sheet, the diaphragm was a polyethylene film, and the electrolyte was 1 mol / L LiPF 6 The product is prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1.

[0212] Experimental Example 1 Material composition and microstructure characterization

[0213] (1) SEM measurement

[0214] The low-sulfur cation-doped ferromanganese pyrophosphate precursors prepared in Examples 1 to 3 were characterized using an emission scanning electron microscope. Figures 1 to 3 As shown, the low-sulfur cation-doped manganese iron pyrophosphate precursors prepared in Examples 1 to 3 all have regular rod-like structures, which are conducive to accelerating the grinding efficiency and nano-crushing, and then being fully mixed with the carbon source and the lithium source to prepare the carbon-coated modified manganese iron lithium phosphate.

[0215] (2) Sulfur content and doping cation content detection

[0216] Take appropriate amounts of the cation-doped pyrophosphate manganese iron precursors obtained in Examples 1 to 4 and Comparative Examples 1 to 5 and the carbon-coated modified lithium manganese iron phosphate in centrifuge tubes, add appropriate amounts of hydrochloric acid, heat and digest for 2 hours, then cool and dilute, and measure using an inductively coupled plasma emission spectrometer.

[0217] (3) Determination of iron and phosphorus content

[0218] The iron and phosphorus contents of the cation-doped pyrophosphate manganese iron precursors obtained in Examples 1 to 4 and Comparative Examples 1 to 5 were measured. Iron content: potassium dichromate titration method was used; phosphorus content: the precursor / lithium manganese iron phosphate was decomposed by perchloric acid, and the carbon in the sample was removed at the same time. In an acidic medium, orthophosphate reacted with quinoline molybdate precipitant to generate a yellow quinoline phosphomolybdic acid precipitate. After filtering, washing, drying, and weighing, the weight of the quinoline phosphomolybdic acid precipitate was obtained, and the phosphorus content in the sample was calculated.

[0219] (4) Tap density

[0220] The cation-doped pyrophosphate manganese iron precursor samples of Examples 1 to 4 and Comparative Examples 1 to 5, which have been weighed, are placed in a three-sided graduated cylinder and placed in a tap density tester. The test time of the density meter is adjusted. After the tap density tester stops vibrating, the cylinder is taken out and the reading is read to calculate the tap density of the powder.

[0221] Test data such as Figures 1 to 3 , as shown in Tables 1 to 2.

[0222] Table 1 Sulfur content in precursor / lithium manganese iron phosphate and main / doping element content and tap density in precursor

[0223]

[0224]

[0225] Note: / indicates that the content of this element was not detected.

[0226] Table 2 Doping metal element content of precursors

[0227]

[0228] Note: 15961 / W means the content of metal W in the precursor is 15961ppm, and the others are similar.

[0229] From the data in Table 1, it can be seen that the sulfur impurity content in the low-sulfur type cation-doped ammonium manganese iron phosphate precursor, low-sulfur type cation-doped pyrophosphate manganese iron precursor and carbon-coated modified lithium manganese iron phosphate prepared by using a phosphate source to treat the metal cation-doped ammonium manganese iron phosphate precursor in Examples 1 to 4 is less than 10ppm, which is much lower than the sulfur content of the metal cation-doped ammonium manganese iron phosphate precursor and carbon-coated modified lithium manganese iron phosphate that are not treated with a phosphate source in Comparative Examples 1 to 3. This is mainly attributed to the addition of an appropriate amount of phosphate source to the synthesized metal cation-doped ammonium manganese iron phosphate precursor in Examples 1 to 4, which can induce recrystallization to expose sulfur impurities and detach from the precursor particles, and then through subsequent filtering and washing post-treatment, the transfer of sulfur impurities is achieved, thereby achieving the purpose of removing sulfur impurities, and improving the crystallinity of the precursor, effectively avoiding the introduction of sulfur impurities when preparing carbon-coated modified lithium manganese iron phosphate. In Comparative Examples 1 to 3, due to the excessive sulfur impurity content in the metal cation-doped ammonium manganese iron phosphate precursor, these impurities were introduced as the core sulfur source during the subsequent preparation of the manganese iron pyrophosphate precursor and lithium iron manganese phosphate, resulting in a high sulfur impurity content in the finished lithium iron manganese phosphate, which seriously limits the performance of the positive electrode material cycle. In addition, after treatment with an additional phosphoric acid source, the ratio of n(Mn+Fe+M):n(P) can be adjusted to be slightly less than 1. The optimization of this ratio not only eliminates the cumbersome step of additionally supplementing the phosphorus source in the subsequent grinding stage, but also forms manganese iron metal site defects inside the lattice, which is conducive to the embedding and extraction of lithium ions, improves structural stability, and significantly improves the crystallinity of lithium iron manganese phosphate, and effectively improves its electrochemical performance.

[0230] From the ICP test results in Table 2, it can be seen that the main element content of the precursors prepared in Examples 1 to 4 and Comparative Examples 1 to 5 is basically consistent with the target doping molar ratio, and the deviation remains within an acceptable range. This result verifies the accuracy of the corresponding element ratio in the precursor expression, further confirms that the cation-doped pyrophosphate manganese iron / ammonium ferric manganese phosphate precursor is successfully prepared according to the preset doping metal element molar ratio, and confirms the uniform distribution of the doping elements therein.

[0231] In summary, through the phosphoric acid source, the sulfur impurity content of the low-sulfur cation-doped pyrophosphate manganese iron precursor and the carbon-coated modified lithium manganese iron phosphate in Examples 1 to 4 is significantly reduced, which is better than the precursors in Comparative Examples 1 to 3 that have not been treated with a phosphoric acid source, and is beneficial to improving the cycle performance of lithium-ion battery positive electrode materials. At the same time, the molar ratio of the main elements in the precursor is also optimized, and the stability of the structure and the electrochemical performance are improved. The ICP test results further verify the accuracy of the element ratio in the precursor and the uniform distribution of the doping elements. Experimental Example 2 Physical properties of carbon-coated modified lithium manganese iron phosphate positive electrode materials and physical and chemical properties of lithium-ion batteries constructed based on the material

[0232] (1) Electrochemical performance test

[0233] The carbon-coated modified lithium manganese iron phosphate material obtained in Examples 1 to 4 and Comparative Examples 1 to 5 was used as the positive electrode active material, and was weighed and dispersed in N-methylpyrrolidone dispersant according to the mass ratio of active material: conductive agent carbon black: binder polyvinylidene fluoride = 94:3:3 to form a uniformly dispersed positive electrode slurry, which was then coated on aluminum foil, vacuum dried at 105°C for 24 hours, and then punched and weighed to obtain a circular electrode. A metal lithium sheet was used as the negative electrode, the obtained electrode sheet was used as the positive electrode, a polyethylene film was used as the diaphragm, and the electrolyte was 1 mol / L LiPF 6 The product was prepared by dissolving in a mixed solvent of dimethyl carbonate (DMC), diethyl carbonate (DEC) and ethylene carbonate (EC) in a volume ratio of 1:1:1 in a 1000 mm glove box (O 2 ≤0.01ppm, H 2 O≤0.01ppm) to assemble 2032 lithium-ion button cells, and then let them stand for 12 hours before conducting electrochemical performance tests at room temperature. The test voltage range was set to 2-4.5V, and the charge and discharge test was conducted at a current rate of 0.1C / 1C. The calculation formula involved is as follows:

[0234] First cycle discharge efficiency = first cycle discharge specific capacity / first cycle charge specific capacity × 100%;

[0235] Capacity retention rate = 100th cycle specific capacity / first cycle discharge specific capacity × 100%.

[0236] (2) Powder compaction density and powder resistance test method

[0237] The carbon-coated modified lithium iron manganese phosphate positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 5 were used as test samples, and the powder compaction was tested using a Yuanneng powder compaction equipment and the powder conductivity was tested using a powder resistivity tester.

[0238] The above measurement results are shown in Table 3

[0239] Table 3 Physical properties of carbon-coated modified lithium manganese iron phosphate positive electrode materials and physical and chemical properties tests of lithium-ion batteries constructed based on the materials

[0240]

[0241] From the data in Table 3, it can be seen that in terms of compaction density, in Examples 1 to 4, since the metal cation-doped ammonium manganese iron phosphate precursor is treated with an appropriate amount of phosphate source to form a low-sulfur cation-doped ammonium manganese iron phosphate precursor, and low-sulfur cation-doped pyrophosphate manganese iron is used as a precursor to prepare the carbon-coated modified lithium manganese iron phosphate material, the compaction density is 2.3 g / cm 3 The above is conducive to improving the energy density of lithium iron manganese phosphate positive electrode materials and the battery performance of subsequent processing into lithium batteries. In contrast, since the metal cation-doped ammonium iron manganese phosphate precursor is not treated with an appropriate amount of phosphate source in Comparative Examples 1 to 3, the tap density of the ammonium iron manganese phosphate precursor is low, and the inside of the precursor is relatively loose. When it is used as a precursor to prepare pyrophosphate manganese iron and lithium iron manganese phosphate, it is not conducive to the use of its compaction density; Comparative Example 4 directly uses low-sulfur cation-doped ammonium iron manganese phosphate precursor to prepare lithium iron manganese phosphate positive electrode materials, so that during the sintering process of lithium iron manganese phosphate, the ammonium iron manganese phosphate decomposes to produce ammonia gas that escapes from the material, resulting in the formation of a loose porous structure in the material, making the material porosity too high, which is not conducive to the improvement of compaction density.

[0242] In terms of powder resistance, the powder resistance of the low-sulfur carbon-coated modified lithium iron manganese phosphate materials prepared in Examples 1 to 4 is lower than 50Ω·cm, showing good conductivity, which is conducive to the performance of its electrochemical performance. In contrast, since Comparative Examples 1 to 3 did not perform an appropriate amount of phosphoric acid source treatment on the metal cation-doped ammonium iron manganese phosphate precursor, its crystallinity, particle morphology and stacking mode were not ideal, making the powder resistance of the material far exceed that of Examples 1 to 4; Comparative Example 4 directly prepared the positive electrode material with a low-sulfur cation-doped ammonium iron manganese phosphate precursor. During the sintering process, the precursor decomposed ammonia, which caused the structure of the positive electrode material to become loose, thereby lengthening the electron migration path in the material, and finally causing the powder resistance to rise sharply; Comparative Example 5 affected the proportion of active substances in the positive electrode material due to the presence of excessive metal doping ions, thereby increasing the powder resistance.

[0243] The electrochemical performance test further shows that the carbon-coated modified lithium manganese iron phosphate cathode materials prepared in Examples 1 to 4 exhibited a more excellent compaction density (>2.3 g / cm 3), first charge specific capacity (>153mAh / g), first coulombic efficiency (>96%), cycle stability (>98%) and lower manganese dissolution (<100ppm) performance. Among them, the lower n(Mn+Fe+M):n(P) ratio helps to construct manganese / iron site defects inside the lithium manganese iron phosphate lattice. These defects can accelerate the migration of lithium ions and alleviate the volume expansion effect during the charge and discharge process, thereby improving the lithium storage performance of the material. On the contrary, Comparative Examples 1 to 3 performed poorly in charge and discharge capacity and cycle stability due to the use of metal-doped ammonium manganese iron phosphate precursors with low tap density, high sulfur content, and high n(Mn+Fe+M):n(P). Comparative Example 4 directly uses a low-sulfur cation-doped ammonium manganese iron phosphate precursor for high-temperature sintering. During the sintering process, the ammonia generated by the decomposition of the ammonium manganese iron phosphate precursor causes a large number of pore defects to form inside the material. These void defects not only reduce the compactness of the material, but also increase its specific surface area. During the charge and discharge cycle, these pore defects will lead to irreversible loss of lithium storage capacity, thus affecting the first cycle coulomb efficiency and cycle stability. In comparative example 5, because the metal doping content in the material is too high, the proportion of effective electrochemically active metal sites in the prepared lithium manganese iron phosphate material is reduced. The excessively doped metal not only cannot contribute to the charge / discharge capacity, but may hinder the migration of lithium ions, thereby having a negative impact on the charge and discharge capacity.

[0244] In summary, this application successfully prepared a low-sulfur cation-doped manganese iron pyrophosphate precursor. By adding an appropriate amount of phosphoric acid source to the prepared metal cation-doped ammonium manganese iron phosphate precursor for treatment, not only the sulfur content in the precursor is greatly reduced, but also the molar ratio of manganese, iron, doping elements and phosphorus elements is regulated to be slightly less than 1, which effectively improves the tap density of the precursor. This precursor can effectively suppress gas generation during high-temperature sintering, avoid pore defects, ensure the compactness of the structure of the obtained carbon-coated modified manganese iron lithium phosphate material, and significantly improve the cycle stability of the material. The lithium-ion battery constructed based on this manganese iron lithium phosphate material exhibits excellent compaction density, charge and discharge capacity and cycle stability.

[0245] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A method for preparing a low-sulfur cation-doped ferromanganese pyrophosphate precursor, characterized in that: The following steps are involved: S1. Using manganese sulfate as a manganese salt to prepare a metal cation-doped ammonium manganese iron phosphate precursor; S2. The cation-doped ammonium manganese iron phosphate precursor obtained in step S1 is mixed with a phosphoric acid source solution, the pH of the solution is adjusted to 7 to 11, the mixture is fully reacted at 50 to 150° C., filtered, the precipitate is washed, and dried to obtain a low-sulfur cation-doped ammonium manganese iron phosphate precursor; S3. The low-sulfur cation-doped ammonium manganese iron phosphate precursor obtained in step S2 is fully calcined at 400 to 600° C. to obtain a low-sulfur cation-doped manganese iron pyrophosphate precursor; Wherein, the metal cation is selected from at least one non-repeating member of Mg, Ti, V, Co, Ni, Cr, Zn, Cu, Zr, Nb, Mo, Al, Ta, W, and Ca; The expression of the low-sulfur cation-doped ferromanganese pyrophosphate precursor is (Mn x Fe 1-x-y M y )2P2O7, 0<x≤0.9, 0<y≤0.1; said M represents one or more metal cation doping; The amount of the phosphoric acid source added is at least 0.1 times the amount of the metal cation-doped ammonium manganese iron phosphate precursor; Steps S1 to S3 are all performed under a protective gas atmosphere.

2. The preparation method according to claim 1, characterized in that: In step S1, the method for preparing the metal cation-doped ammonium manganese iron phosphate precursor specifically comprises the following steps: SI. Preparation of a mixed solution containing manganese sulfate and a doped metal cation salt I; SII. The iron element and the phosphoric acid source solution are mixed and reacted sufficiently to obtain a ferrous dihydrogen phosphate solution system II; SIII. At 70-150° C., the mixed solution I obtained in step SI and the oxidant are added to the ferrous dihydrogen phosphate solution system II obtained in step SII, mixed and reacted sufficiently to oxidize the divalent manganese ions and the divalent iron ions to trivalent manganese ions and trivalent iron ions, respectively, to obtain an intermediate system III, adjust the pH to 7-11, react sufficiently, and post-treat to obtain a metal cation-doped ammonium manganese iron phosphate precursor; Wherein, steps SI to SIII are all carried out under a protective gas atmosphere.

3. The low-sulfur cation-doped ferromanganese pyrophosphate precursor prepared by the preparation method according to claim 1 or 2.

4. A method for preparing carbon-coated modified lithium manganese iron phosphate, characterized in that: The following steps are involved: Si. The lithium salt, the phosphate source, the low-sulfur cation-doped ferromanganese pyrophosphate precursor according to claim 3, the carbon source and the alcohol solution are fully mixed to obtain a slurry, the obtained slurry is ground, and the powder is obtained after drying; Sii. Under a protective gas atmosphere, the powder obtained in step Si is pre-calcined at 450-550° C. for 0.5-8 h, then heated to 650-900° C. for sufficient calcination, and post-treated to obtain carbon-coated modified lithium manganese iron phosphate.

5. The preparation method according to claim 4, characterized in that: In step Si, the molar ratio of the lithium salt, the phosphate source, and the low-sulfur cation-doped pyrophosphate manganese iron precursor is 1: (0.8-1.2): (0.9-1.1).

6. The preparation method according to claim 4, characterized in that: In step Si, the carbon source includes one or more of polyethylene glycol, polyethylene diene, polyvinyl alcohol, glucose, fructose, sucrose, starch, graphene oxide, polyvinyl pyrrolidone, polyvinylidene fluoride, lauric acid, ascorbic acid, and citric acid.

7. The preparation method according to claim 4, characterized in that: In step Si, the mass ratio of the low-sulfur type cation-doped pyrophosphate manganese iron precursor to the carbon source is 1: (0.01-1).

8. Carbon-coated modified lithium manganese iron phosphate prepared by the preparation method according to any one of claims 4 to 7.

9. A positive electrode for a lithium ion battery, characterized in that: It comprises a current collector and a positive electrode active material loaded on the current collector, wherein the positive electrode active material comprises the carbon-coated modified lithium manganese iron phosphate as claimed in claim 8.

10. A lithium ion battery, characterized in that: The invention comprises an electrolyte, a separator, a positive electrode and a negative electrode, wherein the positive electrode comprises the positive electrode of the lithium-ion battery according to claim 9.

Citation Information

Patent Citations

  • Ferromanganese pyrophosphate, lithium ferromanganese phosphate, preparation method of ferromanganese pyrophosphate and lithium ferromanganese phosphate, and battery

    CN117715861A

  • Lithium ferric manganese phosphate-carbon composite material as well as preparation method and application thereof

    CN116825945A

  • Ferromanganese phosphate as well as preparation method and application thereof

    CN117263158A

  • Ferromanganese phosphate as well as preparation method and application thereof

    CN117509597A

  • Preparation method and application of ferric manganese phosphate precursor

    CN118619236A

Cited By

  • High-performance lithium manganese iron phosphate positive electrode material and preparation method thereof

    CN120727814A